Caring for Mum On Country: Exploring the transferability of the Birthing On Country RISE framework in a remote multilingual Northern Australian context. Issue 5 (September 2021) - Ireland, Sarah; Maypilama, Elaine Ḻäwurrpa; Roe, Yvette; Lowell, Anne; Kildea, Sue
Abstract: Background & problem: Birthing On Country (BOC) is an international movement for returning childbirth to First Nations peoples and their communities. The RISE Framework was developed to guide evidence-based BOC implementation but has not yet been tested in a remote Australian community setting. Aim: To test the transferability and acceptability of the RISE Framework in a remote multilingual setting in a Yolŋu (First Nations) community in Northern Australia. Methods: Working in partnership with one remote Yolŋu community, we used a decolonising participatory action research (D-PAR) approach to begin co-designing services and test the acceptability of the RISE Framework. A three-phased transferability process was developed: Warming the ground; Co-Interpreting; and Acceptability Testing. Findings: The RISE Framework was customized to the local Yolŋu context and called 'Caring for Mum on Country'. It was articulated in two languages: Djambarrpuyŋu and English. We successfully used it to guide discussions at a community gathering privileging the voices of senior women to inform the design of local maternity services. Discussion: Using the D-PAR approach, the RISE Framework was readily adapatable to this complex, remote and multilingual setting. It resonated with the Yolŋu community and proved useful for identifying current limitations of existing maternity services and importantly facilitating the design of Yolŋu centred strength-based maternity services. Conclusion: The RISE Framework, combined with our transformative methodology, offers a promising approach to guiding complex interventions for returning services to First Nations communities in diverse contexts. Testing in other settings will further contribute to growing an evidence-base for BOC service planning and implementation.